Is there corporate mindfulness? An exploratory study of Buddhist-enacted spiritual leaders' perspectives and practices - Vu, Mai Chi (Journal of management, spirituality & religion, 2018)
The majority of research on mindfulness reflects a secular viewpoint to the detriment of contextualized mindfulness approaches. We contribute to the literature on organizational mindfulness by arguing that mindfulness is a wisdom-based practice that has been exploited as an instrument for stress reduction or moment awareness techniques. We carried out in-depth interviews in Vietnam with 24 organizational leaders who are Buddhist practitioners, using thematic analysis to elucidate our argument. Our findings reveal that the practice of mindfulness is more effectively a personal and contextual choice rather than a universal "band aid," thus departing from secular interpretations and applications. This choice is based on understanding Buddhist teachings and principles and the combination of the Buddhist qualities of wisdom, compassion, and non-attachment. We argue that this more effectively can enable and contribute to a wise, dynamic, and flexible approach to corporate mindfulness.